Exploring the university-industry linkages and students employability in Malaysia / Shakirah Mohd Saad and Intan Nazrenee Ahmad - Mohd Saad, Shakirah; Ahmad, Intan Nazrenee (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
The university-industry linkages are the well-known strategy that has developed to benefit both university and industry alike. One of the purposes of utilising university-industry linkage is to develop students that can fulfil market needs. Failure to establish sustainable linkage with the industry might bring severe impact to students’ employability. This is a conceptual paper that aims to explore the university-industry linkage and graduate employability in Malaysia. A review of literature spanning from 2012 to 2017 was carried out, after which a proposed framework explaining the antecedents of university-industry linkage is presented. This paper also looked into the areas of academic gap in the university-industry linkage research in Malaysia.